Cerebrospinal fluid promotes survival and astroglial differentiation of adult human neural progenitor cells but inhibits proliferation and neuronal differentiation - Buddensiek, Judith (BioMed Central, 2010)
BACKGROUND: Neural stem cells (NSCs) are a promising source for cell replacement therapies for neurological diseases. Growing evidence suggests an important role of cerebrospinal fluid (CSF) not only on neuroectodermal cells during brain development but also on the survival, proliferation and fate specification of NSCs in the adult brain. Existing in vitro studies focused on embryonic cell lines and embryonic CSF. We therefore studied the effects of adult human leptomeningeal CSF on the behaviour of adult human NSCs (ahNSCs). RESULTS: Adult CSF increased the survival rate of adult human NSCs compared to standard serum free culture media during both stem cell maintenance and differentiation. The presence of CSF promoted differentiation of NSCs leading to a faster loss of their self-renewal capacity as it is measured by the proliferation markers Ki67 and BrdU and stronger cell extension outgrowth with longer and more cell extensions per cell. After differentiation in CSF, we found a larger number of GFAP(+ )astroglial cells compared to differentiation in standard culture media and a lower number of β-tubulin III(+ )neuronal cells. CONCLUSIONS: Our data demonstrate that adult human leptomeningeal CSF creates a beneficial environment for the survival and differentiation of adult human NSCs. Adult CSF is in vitro a strong glial differentiation stimulus and leads to a rapid loss of stem cell potential.